Functional Analysis of FOXE3 Mutations Causing Dominant and Recessive Ocular Anterior Segment Disease. Issue 3 (13th March 2015) - Islam, Lily; Kelberman, Daniel; Williamson, Laura; Lewis, Nicola; Glindzicz, Maria Bitner; Nischal, Ken K.; Sowden, Jane C.
Abstract : Mutation of the lens‐specific gene FOXE3 is associated with congenital malformation of the anterior segment of the eye and glaucoma, though the effect of reported patient mutations on FOXE3 protein have not been investigated. This study examines the effect of four newly identified recessive and two previously reported dominant FOXE3 mutations on transcription factor function. The mutations variably affect FOXE3 DNA binding and transactivation activity and suggest altered mutant protein function rather than a haploinsufficiency underlies the dominant mutations investigated. ABSTRACT: Mutations in FOXE3 are associated with both recessive and dominant inheritance of severe anterior ocular malformations and glaucoma. However, functional analyses of putative pathogenic mutations have not been performed. We tested the hypothesis that variations in FOXE3 activity underlie the different modes of inheritance and disease phenotype. In band shift assays, three recessive mutants showed loss‐of‐function, one retained DNA binding activity, whereas two dominant mutants showed altered activity. All six mutants showed reduced transactivation function compared with wild‐type, and modeling the heterozygous state resulted in an intermediate level of activity providing no evidence for dominant negative action. Our in vitro data are consistent with loss‐of‐function below a dosage sensitive threshold as a mechanism of action for recessive mutations, but indicate an altered mutant protein function rather than a haploinsufficient mechanism for dominant mutations. This study provides the first functional evidence demonstrating that FOXE3 mutations identified in patients impair protein function with differential effects.